The Contemporary World – from Fundamental Crisis to Original Agony?... - Stoyanov, Velcho (UNWE Yearbook, 2015)
In this study we have tried to show and prove that our modern world is in a fundamental (something as universal) crisis causing chaos and even agony. It is contended also by the Global Ecumenical Forum held in Chicago, USA in 1993 but so far things have become more complicated so as in 2007 – 2008 we came upon the global financial and economic crisis holding us still in its arms.Firstly, we make a parallel between the natural and social crises and try to answer whose laws we should follow to live - the natural or social universe laws (by Carl Sagan)? The answer is that we should follow both kinds of laws. We have established, however, that as well as the final or market fundamental model of the market economy and society so as the energy theory and economics obeying the laws of thermodynamics similar to the Stoics underestimate the laws of the social universe and absolute those of the natural one. Precisely on this basis the fundamental crisis is provoked, expanded and deepened and leads towards chaos and agony. Of course the fundamental crisis affects almost the entire “bunch of crises” but we have paid a special attention to two of them – the spiritual and cultural crisis which is the eldest and the most comprehensive and most of all which is typical for the “social universe”. Similar and approximately adequate to the spiritual and cultural crisis is the ecological crisis to “the natural universe” and there is a danger of its turning into an ecological disaster. It is natural that between both universes and their typical crises have an organic unity and interaction as there is between both sides or natures of human beings – the material-physical-biological-instinctive nature and the rational-spiritual one (by Hegel). They are an expression of the universal principles of the dialectics and Holism.We have paid attention to two more specific crises - in the frameworks of the west partnership mainly after 1989 and we have also qualified the Bulgarian transition as a specific crisis with a nature of a peaceful semi-criminal revolution.Unfortunately the fundamental crisis engulfing both universes - the natural and social one - bodes no good to us and if we fail to overcome or mitigate it the consequences could turn out fatal.